Occupational exposures of firefighting and prostate cancer risk in the Norwegian Fire Departments Cohort - Niki Marjerrison; Tom K Grimsrud; Johnni Hansen; Jan Ivar Martinsen; Karl-Christian Nordby; Raymond Olsen; Jo S Stenehjem; Marit B Veierød; Kristina Kjærheim (Scandinavian Journal of Work, Environment & Health)

(untitled)
OBJECTIVES: Excess incidence of prostate cancer (PC) is frequently observed among firefighters; however, the association with specific occupational exposures of firefighting, as well as the influence of a medical surveillance bias, remains unclear. Our aim was to study PC risk within a firefighter cohort, applying indicators of exposures. METHODS: We used indicators of various firefighting exposures to examine PC risk among men in the Norwegian Fire Departments Cohort (N=4251). Incident PC cases, including clinical characteristics, were obtained from the Cancer Registry of Norway (1960–2021). Cox regression was used to estimate hazard ratios (HR) by cumulative exposure in tertiles (reference: lowest) for all, aggressive, and indolent PC, with adjustment for age and birth cohort. The cumulative incidence of PC across birth cohorts and diagnostic periods was examined. RESULTS: No clear associations emerged for any of the exposure indicators, although we observed an HR of 1.31 [95% confidence interval (CI) 0.63–2.72] for aggressive PC in the highest tertile of fire exposure score and 1.31 (95% CI 0.60–2.89) for indolent PC in the highest tertile of inhalation score. Assessment of cumulative incidence demonstrated a greater number of diagnoses at younger ages after 1990, particularly for indolent and unclassifiable PC. CONCLUSIONS: We found little support for an association between firefighting exposures and PC risk. However, our study had few cases in analyses by clinical stage. Challenges in studies of firefighters’ PC risk remain, including difficulties in exposure characterization and the unclear magnitude of a medical surveillance bias.